The external cost of urban mobility - Gallo, Mariano (TeMA - Journal of Land Use, Mobility and Environment, 2008)
Transportation system costs are generally classified in three main groups: the service production costs, the user costs and the external costs. The service production costs are borne by public bodies, enterprises or local authorities as regards the maintenance and construction of infrastructures, and by transit companies as regards the purchase and maintenance of transit vehicles and as regards the management of transit systems. The costs borne by users are mainly private car purchasing, maintenance costs, fuel, highway fares, transit fares, parking fares, etc. The external costs, instead, even if are produced by running and use of transportation systems, are borne by the whole community; indeed, also who does not use the transportation system bears these costs. The external costs usually considered are sometime called social costs, since they impact on the society and represent the externalities of the mobility. The main externalities of mobility are due to greenhouse gas emissions, air pollution, noise, accidents and congestion. Some of these externalities, as air pollution, noise and congestion, produce a sensible reduction of quality of life in urban areas, while the other ones generate high social impacts (accidents) and long-time effects on climate (greenhouse gas emissions). In the literature several studies can be found about the evaluation of external costs. In this paper, after a literature review, some results about the estimation of main external costs in Europe are summarised and discussed.